The Influence of Social Support and Flexible Work Arrangement on Deviant Workplace Behavior with Work-Life Balance as A Mediating Variable: Case Study on Startup Employee in Yogyakarta - Nurfauzi, Muhammad Rifky; Suratman, Andriyastuti (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2024)
This study aims to investigate the influence of social support and flexible work arrangement on deviant workplace behavior, mediated by work-life balance. The research employs a quantitative approach, where primary data is obtained through the use of questionnaires. The respondents of this study are startup employees in Yogyakarta, totaling 169 respondents. Data analysis is conducted using the PLS-SEM method with the SmartPLS 4.0 application. The results of this study indicate that social support and flexible work arrangement have a negative impact on deviant workplace behavior and a positive impact on work-life balance. Furthermore, work-life balance is also found to have a negative impact on deviant workplace behavior. Additionally, the study identifies the mediating effect of work-life balance in the indirect relationship between social support and flexible work arrangement on deviant workplace behavior.